Phoenix Leadership for Business : an Executive's Strategy for Relevance and Resilience - Gokenbach, Valentina (Productivity Press, 2018)
The world continues to ride a wave of turmoil, challenging leaders like never before. New laws, competitive markets and the need to respond to the demands of corporate boards and stockholders unnerve even the most senior of leaders resulting in progressively shorter tenures of those in leadership positions. The modern leader needs to be increasingly resilient and their leadership must be entirely relevant to their organizations and the industry. Phoenix Leadership for Business: An Executive's Strategy for Relevance and Resilience provides a brand new, innovative concept, that of the Phoenix Leader, with proven strategies and approaches to evolve your leadership approach to one that is flexible, powerful and effective. This book utilizes the strong metaphor of a Phoenix and identifies all of the necessary techniques that leaders need to improve profitability, resource management and organizational success thus improving their relevance to the company. This book introduces a new paradigm created by Val Gokenbach for leadership in complex organizations and provides effective strategies that will guide leaders in the business field. Val possesses a doctoral degree in Management and organizational leadership and over 40 years of experience as a healthcare executive. She is also a leadership consultant, professor, executive coach and author on leadership topics. You, as a business leader, will learn to reinvent yourself by putting her proven concepts into effect to become a Phoenix in your organization.